(untitled) (Jurnal Ilmiah Teknik Sipil, 2026)
Concrete is one of the most widely used materials in the construction of buildings, bridges, and infrastructure thanks to its compressive strength, durability, and relatively low production cost. However, its main weakness lies in its vulnerability to high temperatures. When exposed to fire, concrete can suffer significant quality degradation through both physical mechanisms (such as water evaporation, thermal cracking, and spalling) and chemical changes (like the decomposition of calcium hydroxide and damage to C-S-H gel). This study investigates how exposure to high temperatures up to 500°C affects the performance of low-strength concrete (f’c ≈ 12 MPa), with a particular focus on residual compressive strength and visible surface changes after a fire. The research combines a literature review with a planned laboratory experiment using cylindrical concrete specimens exposed to 200°C, 300°C, 400°C, and 500°C. Findings show that concrete remains relatively stable up to 200°C, with a strength reduction of less than 5%. Between 300°C and 400°C, strength drops significantly up to 28% and microcracks begin to form. At 500°C, concrete loses over 40% of its strength, accompanied by a noticeable color shift to whitish-gray and the appearance of wide cracks. These symptoms point to irreversible microstructural damage. This research is intended to support post-fire safety assessments, especially for buildings constructed with lower-grade concrete. The results confirm that exposure to around 500°C is sufficient to render a structure unsafe mirrored by the real-life case of a school fire in Penajam, where the building was ultimately demolished due to concrete degradation. Keywords: concrete, fire, compressive strength, high temperature, low-strength concrete.